Why people snap : an exploratory study of QR code marketing in Singapore. - Tay, Xiang Yi. (2013)
QR code has emerged as a refreshing tool in the digital marketing landscape in Singapore over the past year. Its arrival came at an optimal time given Singapore’s high smartphone penetration rate and progressive Information Technology (IT) infrastructure. Despite its novelty as an attraction point and its unique ability to bridge offline and online media, there is a seemingly lack of enthusiasm amongst consumers in adopting the technology. With no precedent in the academic study of QR codes in Singapore, an exploratory study is conducted to examine the effectiveness of QR code marketing among youths in Singapore.